(untitled) (Islas, 2025)
Introduction: This research examines the use of certain impolite forms employed during doctoral thesis defenses in the Physical Culture program, based on the power/solidarity axis that emerges in these academic exchanges. Methods: Sociolinguistic and intercultural pragmatics methods from theories of verbal politeness were applied to ensure adequacy to the academic context of scientific thesis defenses. Results: The impolite uses analyzed reveal their presence in doctoral thesis defenses and the violation of sociocultural norms expected in these formal events. Although the norm prescribes politeness, dialogue culture, and respect for others’ opinions, evidence showed noncompliance with these conventions, causing clear damage to the social image of the interlocutors. Conclusions: Verbal impoliteness in doctoral defense events affects the social image of the interlocutors. The linguistic forms studied reflect aggressive behaviors on the part of both the committee and the doctoral candidate, as characteristic features of the symmetric power axis.